Pengaruh Profitabilitas, Solvabilitas dan Audit Tenure Terhadap Audit Delay - Farida Asfiah; Ajeng Dwi Rahayu; Cris Kuntadi (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
This study aims to determine the effect of Profitability, Solvency, and Audit Tenure on Audit Delay. The purpose of writing scientific articles is to find out the hypothesis of influence between variables, which can be used in future research. This research uses qualitative descriptive methods and library research accessed through Google Scholar, e-books, and other online media. The result of writing this literature review article is: Profitability and Solvency have a positive insignificant effect on Audit Delay, Audit Tenure has a significant effect on Audit Delay.